Log in to add a comment

## Answers

+ = 1

where b is the y-intercept and a is the x-intercept.

Find y -intercept by setting x to 0:

2x + 3y = 1

2(0) + 3y = 1

3y = 1

3y/3 = 1/3

y = 1/3 ⇒

**y-intercept (b) = 1/3**

Find x-intercept by setting y to o:

2x + 3y = 1

2x + 3(0) = 1

2x = 1

2x/2 = 1/2

x = 1/2 ⇒

**x-intercept (a) = 1/2**

INTERCEPT FORM:

+ = 1

INTERCEPT FORM:

----------------------------

To change the given equation 2x + 3y = 1 to slope-intercept form:

2x + 3y = 1

3y = - 2x + 1

3y/3 = - 2x/3 + 1/3

y = -